Comparison of Etest, Disk Diffusion, and Broth Macrodilution for In Vitro Susceptibility Testing of Rhodococcus equi - Berghaus, Londa J. (J Clin Microbiol, 2014)
MICs of erythromycin, clarithromycin, azithromycin, rifampin, gentamicin, and doxycycline against 101 isolates of Rhodococcus equi were determined by broth macrodilution, disk diffusion, and Etest. Categorical agreement ranged between 85.1 and 100%. Overall, the agreement between Etest and disk diffusion was better than the agreement between broth macrodilution and the agar-based methods.